Crime of Embezzlement in Employment Relationship - Darwati Darwati (Faculty of Law, Universitas Pekalongan, 2020)
The worker was accused of embezzlement in the purchase of lunch boxes. Due to this incident, the worker was asked to resign. However, because the worker had no intention of taking control of the money, the worker refused the request from personnel to resign. For this refusal, the worker was reported to the police on charges of violating Article 372 and Article 374 of the Criminal Code. This study aims to analyze and find out the duties and authority of personnel in the company, then whether the worker's mistake is included in the violation and analyze the legal considerations of the Panel of Judges Number 1320/Pid.B/2019/PN.JKT.TIM whether it is in accordance with the applicable regulations. The research methods used are normative juridical and sociological juridical. The results showed that Personnel have the authority to provide guidance to workers if they make mistakes or violate company rules. Workers' mistakes are not included in violations of Criminal Code 372 or Criminal Code 374. Decision of the Panel of Judges Number 1320/Pid.B/2019/PN. JKT. TIM violates Article 2 of Indonesian Supreme Court Regulation Number 2 of 2012 concerning Adjustment of the Limits of Minor Crimes and the Amount of Fines in the Criminal Code, Limited Liability Company Law.